Promotion and practice of an online service offering Traditional Chinese Medicine constitution conditioning under the normalization of epidemic prevention and control (疫情防控常态化背景下中医体质调理服务线上推广与实践) - MA Qian (马茜); YU Hong (俞红); XU Junhua (徐俊华); XU Lidan (许丽丹); FANG You (方友); ZHEN Yanping (郑艳平); LI Yanlan (李燕兰); LIANG Xiao (梁肖); LU Mingya (陆明雅); ZHANG Yijun (张轶俊) (Association of Integrative Nursing, 2022)
Objective To explore the feasibility and effectiveness of an online service offering Traditional Chinese Medicine (TCM) physique conditioning under the normalization of epidemic prevention and control. Methods From March 1, 2020 to March 10, 2020, 190 subjects who were judged as "Qi deficiency" by "TCM constitution test" were recruited online. A research team was set up to develop physique conditioning plans, formulate "Ear Massage", construct a physique conditioning WeChat group and public account for Qi-deficiency subjects, and provided online physique conditioning services for 6 months. The conversion score of Qi-deficiency, the frequency of respiratory infection in 6 months and psychological status were compared before and after intervention. Results Compared with before intervention, the conversion score of Qi-deficiency, the frequency of respiratory infection in 6 months, the negative emotion score and total score of the five dimensions of depression, nervous decline, fear, compulsion-anxiety and hypochondria of the subjects decreased, with statistical significance(P<0. 01). Conclusion The online service of TCM constitution conditioning can regulate TCM constitution, prevent respiratory tract infection and regulate negative emotions of Qi-deficiency people susceptible to the virus, and can be popularized under the normalization of epidemic prevention and control. (目的 探讨疫情防控常态化背景下线上中医体质调理服务推广的可行性和有效性。方法 2020年3月1日-3月10日, 通过线上方式招募经"中医体质测试"判断为"气虚质"的受试者190例。成立课题小组, 制订体质调理方案, 编制"扶正耳穴操", 构建气虚质体质调理微信群及公众号, 对气虚质受试者进行为期6个月的线上体质调理服务。比较干预前后气虚质转化分、6个月内呼吸道感染次数及心理状况。结果 与干预前比较, 研究对象的气虚质转化分, 6个月内呼吸道感染次数, 抑郁、神经衰落、恐惧、强迫-焦虑、疑病5个维度的负面情绪评分及总分均下降, 差异有统计学意义(P＜0. 01)。结论 针对气虚质病毒易感人群的线上体质调理服务可调理体质、预防呼吸道感染、调节负性情绪, 在疫情防控常态化形式下, 可推广使用。)